The Long and Winding Road of Christian Education Teachers in Fulfilling the Divine Vocation: Should You Run Away from Reality or Give Up with Circumstances? - Sandy Ariawan; Diana Situmeang; Peringatan Zebua; Kristyana Kristyana; Pangeran Guntar Wijaya Baringbing (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2021)
The entire long series of educational processes, from material preparation, delivery, evaluation, to the selection of technology as a means of learning may be a series of difficult and painful problems, especially during pandemic Covid-19.Teachers are faced with the fact that Christian values are suspected of declining in their students. Not to mention the pressure that is always given, that religious lessons only succeed if there is a change in behavior in learners. This research aims to prove that the understanding of the Divine vocation as a teacher makes the teachers of Christian education able to survive in the situation of the Covid-19 pandemic. The study used quantitative methods, to look at teachers' understanding of their Divine vocation. The variables used in this study were the teacher's level of understanding of Divine vocation as independent variable and teacher’s competence as dependent variable, with a sample of 50 people.It can be concluded that there is an influence between the teacher’s level of understanding of Divine vocation on the teacher’s competence of Christian education. This can be seen from the results of the R-Square determination coefficient which shows a figure of 0.521 which means that the influence of independent variables (X) on dependent variable changes (Y) is 52.1% while the remaining 47.9% is influenced by variables other than independent variable X (the teacher’s level of understanding of Divine vocation). The problem of decadence of teacher’s competence, that is very likely experienced by teachers during this pandemic, can be addressed by putting full emphasis on the importance of understanding a teacher's Divine vocation.